A wearable system for biosignal monitoring in weightlifting - Mercado-Aguirre, I. M.; Mercado-Medina, E. L.; Chavarro-Hernandez, Z. D.; Dominguez-Jimenez, J. A.; Contreras-Ortiz, S. H. (Sports Engineering, 2017)
The use of technological aids in sports has increased in the last years. These tools allow to register the athletes` movements to evaluate and track their performance over time. With that information, it is possible to design more effective training routines, prevent and treat injuries, and improve performance. This paper describes the design and construction of an electronic system to register joint angle and electromyography signals during the execution of weightlifting exercises. The system was designed to be unobtrusive, energy efficient, and low cost. It was evaluated during the execution of flexion/extension exercises of the arm with weights, and was effective to acquire the signals and transmit them wirelessly in real-time. Electromiography signals were visualized and analyzed with an adequate dynamic range, and angle measurements were performed with error percentages less than 0.8 %.